Мне нравится Паскаль - Поддубная Л. М. (Научно-популярная библиотека школьника, 1992)
Экземпляры: КХ (19971106) / Инвентарный номер: 1010779 / Цена: / Сис.шифр: 32.973 / Авт.знак: П 44 / ГРНТИ: 50 / ББК: 32.973.2-018.1